Revisiting an ‘old’ antibiotic class polymyxins by drug combination therapy targeting Gram-negative superbugs: Toyyiban perspective - Mahamad Maifiah, Mohd Hafidz; Abdullah Sani, Muhamad Shirwan; Abd Rahim, Nusaibah (HH Publisher, 2019)
The Islamic concept of halalan-toyyiban encompasses medicines and pharmaceuticals. Halal pharmaceuticals mean the products are free from any unlawful (haram) constituents while in another aspect, toyyib pharmaceuticals particularly concern on the products’ wholesomeness, quality and safety. Polymyxins, an ‘old’ class antibiotic have been employed as the last-line defence for infections caused by multidrug-resistant (MDR) Gram-negative pathogens. Nevertheless, the exceptional clinical applications of polymyxins are restrained due to their dose-limiting nephrotoxicity and neurotoxicity. In addition, pharmacokinetic/pharmacodynamic (PK/PD) studies indicate that polymyxin monotherapy often fails to achieve an effective in vivo plasma exposure concentration, potentially lead to the emergence of bacterial heteroresistance. To optimise the significant potential of polymyxins, therefore, polymyxin combination therapy has been recommended. The strategy provides some advantages as it significantly confers safer clinical dosage of polymyxins administration thus likely to reduce its toxicity effects. Looking from the toyyiban perspective, this review discusses on the synergistic killing of polymyxin combination for the treatment of MDR Gram-negative infection to reduce its potential toxicity and emergence of resistance.